Insentif Halal Produk Terhadap Konsumsi Makanan Dan Minuman Dalam Industri Kreatif - Nida Husnia Zahra (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2020)
As a country with a Muslim majority, Indonesia should be the center for the development of the Islamic economy in the world. The potential to get there is already there, starting from halal certification, concern for Muslim-friendly products, and services that make it easier for Muslims to practice their faith. The strategy to achieve Indonesia's vision as a leading Islamic economic center in the world is to strengthen the halal value chain. Inside there are a number of industries related to the needs of the Muslim community which are divided into several clusters. Products that are certified halal have a large market opportunity, with estimates that the marketing of halal products in the global market has reached good quality and quantity. This of course will affect people's consumption of these foods and beverages, especially for the Muslim community.